Current Therapy and Therapeutic Targets for Microsporidiosis - Wei, Junhong; Fei, Zhihui; Pan, Guoqing; Weiss, Louis M.; Zhou, Zeyang (Frontiers in Microbiology, 2022)
Microsporidia are not only opportunistic pathogens in humans, but are also an emerging threat for animal husbandry. They cause chronic diarrhea in immune-compromised patients. Infection is associated with increased mortality. In addition, to their role in pébrine in sericulture, the prevalence and severity of microsporidiosis in beekeeping and aquaculture has increased markedly in recent decades. Therapy for these pathogens in medicine, veterinary, and agricultural use has become a recent focus of attention. Currently, only a few antimicrosporidial drugs are commercially available. New therapeutic agents are needed for these infections and this is an active area of investigation. In this article we provide a comprehensive summary of current and some promising new agents for the treatment of microsporidiosis including: albendazole, fumagillin, nikkomycin, orlistat, synthetic polyamines, and quinolones. Therapeutic targets which could be utilized for the design of new drugs are also discussed including: tubulin, type 2 methionine aminopeptidase, polyamines, chitin synthases, topoisomerase IV, triosephosphate isomerase and lipase. We also summarize complementary and alternative medicine strategies including herbal extract, propolis, and probiotics. This review should help facilitate the drug development for combating microsporidiosis.